Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2013-03-17T11:21:14+04:00

1) 2ab             a-b          2ab                     a-b             4ab+(a-b)^2          4ab+a^2-2ab+b^2

  -----------  +---------- = --------------  + -----------      = ------------------  =  ---------------------------  =

  a^2-b^2       2a+2b     (a-b)(a+b)        2(a+b)         2 (a-b)(a+b)                2(a-b)(a+b)

 

     2ab+a^2+b^2             (a+b)^2                 a+b

= ---------------------  = --------------------  = ------------

        2(a-b)(a+b)            2(a-b)(a+b)         2(a-b)

 

2)   a+b              2a           (a+b) * 2a            a

     --------   *  ---------  = ------------------- = ----------

      2(a-b)        (a+b)        2(a-b) (a+b)        a-b

 

3) a         b               a              b            a-b

  ----- +---------  = ---------  - ---------  = --------  = 1

   a-b        b-a         a-b         a-b            a-b

Ответ:1